1984
DOI: 10.1016/0304-3959(84)90808-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain alleviation by vibratory stimulation

Abstract: In the present study 366 patients suffering acute or chronic musculoskeletal pain of different origin were given vibratory stimulation for the pain. Many of the patients had previously had treatments of various kinds without satisfactory relief. The effect of vibratory stimulation was assessed during and after stimulation using a graphic rating scale. Sixty-nine per cent of the patients reported a reduction of pain during vibratory stimulation. The best pain reducing site was found to be either the area of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
1
6

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(115 citation statements)
references
References 19 publications
9
95
1
6
Order By: Relevance
“…4 Other receptors, including Meissner's corpuscles in the skin or others in the subcutaneous tissues and bone also contribute. 5 It has been suggested that it is the large diameter fibres within the area directly affected by pain that, when stimulated, will achieve maximum pain reduction. 6 This neural gate is proposed to lie within the spinal cord ⁄ brainstem and inhibits transmission of nociceptive action potentials to higher centres in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Other receptors, including Meissner's corpuscles in the skin or others in the subcutaneous tissues and bone also contribute. 5 It has been suggested that it is the large diameter fibres within the area directly affected by pain that, when stimulated, will achieve maximum pain reduction. 6 This neural gate is proposed to lie within the spinal cord ⁄ brainstem and inhibits transmission of nociceptive action potentials to higher centres in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…8 In the orofacial region vibration stimuli are easily applied, and have been used to raise the pain threshold; [9][10][11] to relieve pain of dental origin whether pulpal, periodontal, or post-surgical; 12 to help manage chronic intractable orofacial pain 2 and acute or chronic musculoskeletal pain. 5,13 Furthermore, it has been suggested that pain reduction is greatest in the orofacial region if the source of vibration is applied not only within the area directly affected by pain, but when the firmness of vibration application stimulates the underlying bone on the same side as the pain. 2 The use of vibration stimuli during a common painful dental procedure such as local anaesthetic injections has been restricted to a vibrating needle 14 or a vibrating swab for topical anaesthetic application, 15 although this is not the typical method for vibration application.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration is a modality that has shown efficacy in the treatment of chronic musculoskeletal pain, 15,16 suggesting promise for the treatment of DOMS as well. Whereas the effects of vibration on muscle pain from DOMS have not been widely studied, inconsistent and conflicting results have been reported.…”
mentioning
confidence: 99%
“…Previous studies also suggest that the improvement in ROM by vibration is associated with pain alleviation (Lundeberg et al, 1984;Pantaleo et al, 1986), increase in blood flow (Kerschan-Schindl et al, 2001), relaxation of stretched muscles (Turnbull et al, 1982) and inhibition of muscular antagonist mediated by the Golgi tendon organ -Iβ afferent neuron pathway (Bove et al, 2003).…”
Section: Joint Flexibilitymentioning
confidence: 97%